Further insight into prognostic factors in endometrial cancer: the new serum biomarker HE4. Issue 1 (2nd January 2017) - Capriglione, Stella; Plotti, Francesco; Miranda, Andrea; Lopez, Salvatore; Scaletta, Giuseppe; Moncelli, Michele; Luvero, Daniela; De Cicco Nardone, Carlo; Terranova, Corrado; Montera, Roberto; Angioli, Roberto
ABSTRACT: Introduction : Endometrial cancer (EC) is one of the most common gynecological cancer worldwide. To date, no good markers are routinely used in clinical practice for prognosis and monitoring. Areas covered : During the last years, an increasing interest in literature has been growing on HE4 (Human epididimis 4). Therefore, we aimed to gather all the evidence reported in literature analysing the potential prognostic value of HE4, compared to the well know tumor's features (histological type and grade, stage of disease, depth of myometrial invasion, lymphovascular space involvement and cervical involvement). Expert commentary : The analysis of data suggests that HE4 seems to have a good performance in prognosis and monitoring of the disease, helping to schedule the appropriste timing of imaging and surgery in a more individualized fashion. However, these findings surely require a validation in a larger cohorts of patients. Probably, in the next five years, prospective randomized trials will be performed to confirm the prognostic role of HE4 in EC and to find a tailored EC management strategy.